A comparative study of effects of extraction solvents/techniques on percentage yield, polyhenolic composition, and antioxidant potential of various extracts obtained from stems of Nepeta leucophylla: RP‐HPLC‐DAD assessment of its polyhenolic constituents. Issue 2 (12th October 2016) - Sharma, Ajay; Cannoo, Damanjit Singh
Abstract: In the present study, the methanol, chloroform, and hexane extracts were isolated from the stems of Nepeta leucophylla using maceration method, soxhlet extraction method, and ultrasonic assisted extraction method. These extracts were analyzed for their total flavonoids content (TFC), total polyphenolic content (TPC), and antioxidant potential using nitric oxide scavenging (NOS), DPPH˙ (2, 2‐diphenyl‐1‐picrylhydrazyl radical scavenging), total antioxidant capacity (TAC), and ferric reducing antioxidant power (FRAP) assays. The results of percentage yield, TPC, and TFC for various extracts varied from 0.99 to 12.16%, 0.34 to 133.7 mg GAE/g DPE, and 20.21 to 282.74 mg RE/g DPE, respectively, whereas the results of antioxidant potential of TAC, FRAP, percentage inhibition of NO and DPPH˙ scavenging activity ranged from 0.11 to 40.74 mg AAE/g DPE, 4.41 to 148.65 mg Fe (II) E/g DPE, 1.29 to 35.56%, and 14.93 to 90.43%, respectively. Practical applications: N. leucophylla is an important wild Himalayan aromatic plant. Traditionally, it is used for the cure of malarial fever and its leaves are consumed as herbal tea. It is also known to have antifungal and antibacterial activity. The present results indicate that the SEM is the best technique for the isolation of naturally occurring antioxidants (NOAs) using methanol as a solvent from the powdered stem of N. leucophylla . Our research findings also indicate that the various extracts obtained from the stem of N. leucophylla show high antioxidant potential (FRAP, TAC, NO, and DPPH˙ radical scavenging activity) and are rich source of different NOAs viz. polyphenolics, flavonoids, coumarins, steroids etc. These classes of NOAs are also well known for their therapeutic potential like antitumor, anti‐inflammatory, antiviral, antimicrobial, and antifungal properties. Hence, the stem of N. leucophylla may play a promising role in health benefits, pharmaceutical, nutraceutical, and functional foods development.